The role of customer imagination in the effect of electronic word-of-mouth and brand identity on purchase intention: A study of domestic cosmetic enterprises - Tran Le Hoang , Ngoc; Mai Thi My, Quyen; Le Nguyen, Hau; Nguyen Tien, Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
Vietnamese domestic cosmetic enterprises are increasingly utilizing online platforms to enhance brand identity and stimulate purchase intention. Furthermore, cosmetics consumers typically conduct extensive research and alternative evaluations, as well as imagine how the product will perform for them before making a purchase. While contemporary consumer behavior indicates a growing reliance on electronic word-of-mouth (e-WOM) from peer consumers as a primary source of information, the mechanisms by which perceived e-WOM and brand identity translate into purchase intention, mediated by consumer imagination, remain uninvestigated. To address this gap, a conceptual model was developed and tested using structural equation modeling with data from 256 consumers who had engaged with e-WOM about domestic cosmetic products. The findings establish a theoretical framework demonstrating how imagination acts as a mediator, turning e-WOM and brand identity into consumer purchase intention. Specifically, e-WOM is found to positively influence both brand identity and imagined benefits. Brand identity is shown to amplify the two outcomes of imagination, including imagined benefits and imagined emotions. These two imagination outcomes subsequently contribute to an increase in consumer purchase intention. Meaningful theoretical contributions and managerial implications are proposed based on these findings.